Principles of electric machines and power electronics, second edition - Sen, Paresh C. ([S.l.] : John Wiley & Sons, Inc., 1996)
This new edition combines the traditional areas of electric machinery with the latest in modern control and power electronics. It includes coverage of multi-machine systems, brushless motors and switched reluctance motors, as well as constant flux and constant current operation of induction motors. It also features additional material on new solid state devices such as Insulated Gate Bipolar Transistors and MOS-Controlled Thrysistors.